1984
DOI: 10.1007/bf00384263
|View full text |Cite
|
Sign up to set email alerts
|

Ant distribution patterns in a cameroonian cocoa plantation: investigation of the ant mosaic hypothesis

Abstract: Investigation of the spatial distribution of tropical ant species has shown that in tree crop plantations, abundant species have mutually exclusive distributions generated by competition thus forming a 'mosaic' of territories in the tree canopies. This study compares the spatial distribution of ants which live in the trees with that of ants which live on the ground in a cocoa plantation in Southern Cameroon. It shows that while tree-dwelling ants maintain mutually exclusive distributions, the distributions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
86
0
5

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(97 citation statements)
references
References 28 publications
6
86
0
5
Order By: Relevance
“…In arboreal ant assemblages, dominant species defend "absolute territories"-discrete spatial units extending beyond the location of individual food or nest resources. This leads to a patchy distribution of ant species across the forest canopy, known as an ant mosaic (Room 1971(Room , 1975Jackson 1984;Dejean et al 2007). Outside forest ecosystems, the arboreal patterns of ant species coexistence and competition are not well documented.…”
Section: Introductionmentioning
confidence: 99%
“…In arboreal ant assemblages, dominant species defend "absolute territories"-discrete spatial units extending beyond the location of individual food or nest resources. This leads to a patchy distribution of ant species across the forest canopy, known as an ant mosaic (Room 1971(Room , 1975Jackson 1984;Dejean et al 2007). Outside forest ecosystems, the arboreal patterns of ant species coexistence and competition are not well documented.…”
Section: Introductionmentioning
confidence: 99%
“…Given the importance of honeydew as a resource, it is expected and often observed that nutritious trophobioses are defended by ants against competitors and effectively monopolised (Jackson, 1984;Dejean et al, 1997;Blüthgen et al, 2000bWimp and Whitham, 2001;.…”
Section: Introductionmentioning
confidence: 99%
“…Food resources which are predictable in space and time, such as plant affiliated homopterans or nectaries, offer themselves for systematic use and monopolisation since they can be effectively exploited and defended (as is shown in ant mosaics on trees, e. g., Strickland, 1951;Jackson, 1984;Blüthgen et al, 2000). The most systematic and economical resource use has probably been achieved by individual ants specialising on small and clearly defined predictable foraging sites (Lachaud et al, 1984;Fourcassié and Traniello, 1993).…”
Section: Introductionmentioning
confidence: 99%